Competitive and segmented informal labor markets - Isabel Günther; Andrey Launov (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
It has recently been argued that the informal sector of labor markets in de- veloping economies shows a dual structure with part of the informal sector being competitive to the formal sector and part of the informal sector being the result of market segmentation. To test this hypothesis, we formulate an econometric model which allows for a heterogeneous informal sector with unobserved individ- ual sector a±liation in the informal sector and which takes into account selection bias induced by the employment decision of individuals. Our empirical results for the urban labor market in C^ote d'Ivoire show the existence of both competitive and segmented employment in the informal sector.
Keywords: J42; O17; 330